Video Demonstrations of a Benzene Derivative Reaction from Its Optimized Intermediate Structure - Awal, Jumaidil; Martoprawiro, Muhamad Abdulkadir (J-PEK (Jurnal Pembelajaran Kimia), 2023)
A number of researchers have performed studies on the application of chemical reaction visualization by means of computational chemistry techniques for the purpose of teaching and learning chemistry at secondary and higher education levels. However, on practical grounds, the presented approach thus far was generally unattainable for teachers due to the time-consuming process of finding the transition states. This research offers a less time-consuming computational chemistry technique for producing organic reaction-modelling videos upon which the students may sufficiently build their understanding of fundamental concepts of chemical reactions. The technique being proposed here consists of (1) intermediate structure modelling, (2) reactant-wise and product-wise optimizations of the intermediate structures without the search for transition states, and (3) visualizations of the optimized results. The application of this technique has managed to produce a video demonstration of an organic reaction of benzene derivatives that may serve as modelling videos in chemistry lessons at secondary education or undergraduate degree levels.REFERENCESBode, B. M., & Gordon, M. S. (1998). Macmolplt: A graphical user interface for GAMESS. Journal of Molecular Graphics and Modelling, 16(3), 133–138. https://doi.org/10.1016/S1093-3263(99)00002-9Carey, F. A. (2000). Organic chemistry (4th ed). McGraw-Hill.Cohlberg, J. A. (2021). Exploring Proteins and Nucleic Acids with Jmol. W. H. Freeman and Company. https://home.csulb.edu/~cohlberg/Jmolmanual.pdfCramer, C. J. (2004). Essentials of computational chemistry: Theories and models (2nd ed). Wiley.Hanwell, M. D., Curtis, D. E., Lonie, D. C., Vandermeersch, T., Zurek, E., & Hutchison, G. R. (2012). Avogadro: An advanced semantic chemical editor, visualization, and analysis platform. Journal of Cheminformatics, 4(1), 17. https://doi.org/10.1186/1758-2946-4-17Ikuo, A., Ikarashi, Y., Shishido, T., & Ogawa, H. (2006). User-Friendly CG Visualization with Animation of Chemical Reaction: Esterification of Acetic Acid and Ethyl Alcohol and Survey of Textbooks of High School Chemistry. Journal of Science Education Japan, 30(4), 210–215.Ikuo, A., Nagashima, H., Yoshinaga, Y., & Ogawa, H. (2009). Calculation of potential energy in the reaction of "I + H2 → HI + H" and its visualization. 6.Ikuo, A., Nagashima, H., Yoshinaga, Y., & Ogawa, H. (2011). Development of teaching material in tablet computer based on computer graphics by quantum chemistry calculation – Reaction of I + H2 → HI + H. Work-in-Progress Poster of the International Conference on Computers in Education: ICCE 2011, 31–33.Ikuo, A., & Ogawa, H. (2014). Visualization of Reaction Mechanism by CG Based on Quantum Chemical Calculation—An Approach to Electronic Laboratory Textbook -. African Journal of Chemical Education, 4(3), 22–33.Ikuo, A., Saito, K., Yoshinaga, Y., & Ogawa, H. (2013). Development of Teaching Material in Tablet PC for Experiment of Nitration of Benzene Based on Computer Graphics by Quantum Chemical Calculation. Work-in-Progress Poster of the International Conference on Computers in Education: ICCE 2013, 21–23.Koreeda, M. (2011). Chem 216 S11 Notes [Lab work notes].  http://websites.umich.edu/~chem216/216% 20S11-Expt%201.pdfLevine, I. N. (2009). Physical chemistry (6th ed). McGraw-Hill.Lewars, E. G. (2016). Computational Chemistry: Introduction to the Theory and Applications of Molecular and Quantum Mechanics. Springer.Mendera, I. G. (2020). Kimia: Benzena dan Turunannya. Direktorat SMA Ditjen PAUD, Dikdas, dan Dikmen Kemendikbud.Neese, F., Wennmohs, F., Becker, U., & Riplinger, C. (2020). The ORCA quantum chemistry program package. The Journal of Chemical Physics, 152(22), 224108. https://doi.org/10.1063/5.0004608Nursanti, Y. I. (2020). Modul Tema 15: Berpadu dan Bersenyawa. Direktorat Dikmas dan Diksus Ditjen PAUD, Dikdas, dan Dikmen Kemendikbud.Omer, R., Koparir, P., Ahmed, L., & Koparir, M. (2020). Computational determination the reactivity of salbutamol and propranolol drugs. Turkish Computational and Theoretical Chemistry, 4(2), 67–75. https://doi.org/10.33435/tcandtc.768758Polik, W. F., & Schmidt, J. R. (2022). WebMO: Web‐Based Computational Chemistry Calculations in Education and Research. WIREs Computational Molecular Science, 12(1), e1554.Putri, P. (2016). Tata Nama Senyawa dan Perhitungan Kimia—Karakteristik Peserta Didik. P4TK Bisnis dan Pariwisata Ditjen GTK Kemendikbud.Rahayu, I. (2009). Praktis Belajar Kimia untuk Kelas XII SMA/MA Program IPA. Pusat Perbukuan Depdiknas.S. Fernandes, H., Ramos, M. J., & M. F. S. A. Cerqueira, N. (2018). molUP: A VMD plugin to handle QM and ONIOM calculations using the gaussian software: A VMD Plugin to Handle QM and ONIOM Calculations. Journal of Computational Chemistry, 39(19), 1344–1353. https://doi.org/10.1002/jcc.25189Schaftenaar, G., Vlieg, E., & Vriend, G. (2017). Molden 2.0: Quantum chemistry meets proteins. Journal of Computer-Aided Molecular Design, 31(9), 789–800. https://doi.org/10.1007/s10822-017-0042-5Wardiyah. (2016). Kimia Organik. BPPSDMK Pusdik SDM Kesehatan Kemenkes.